Search for a pseudoscalar boson decaying into a Z boson and the 125 GeV Higgs boson in l(+)l(-)b(b)over-bar final states - Khachatryan, V. (2015)
Results are reported on a search for decays of a pseudoscalar A boson into a Z boson and a light scalar h boson, where the Z boson decays into a pair of oppositely-charged electrons or muons, and the h boson decays into bb. The search is based on data from proton-proton collisions at a center-of-mass energy root s = 8 TeV collected with the CMS detector, corresponding to an integrated luminosity of 19.7 fb(-1). The h boson is assumed to be the standard model-like Higgs boson with a mass of 125 GeV. With no evidence for signal, upper limits are obtained on the product of the production cross section and the branching fraction of the A boson in the Zh channel. Results are also interpreted in the context of two Higgs doublet models. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.